ANALYSIS OF THE LEVEL OF WELFARE OF THE FISHERMAN COMMUNITY IN ALUE AMBANG VILLAGE TEUNOM DISTRICT ACEH JAYA DISTRICT (Walfare Analysis of Fisherman Communitie in Alue Ambang Village Teunom District Aceh Jaya Regency) - Rusdi Faizin; Isma Suryani (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to determine the level of welfare of fishing communities in the same Ambang Village teunom district of Aceh Jaya Regency. The sample in this study amounted to 30 people representing a population of 60 fishermen. Data analysis obtained from the results of the study was analyzed using quantitative descriptive methods based on 8 indicators of BPS welfare criteria. The data obtained from the distribution of frequency and percentage and then presented in the form of a table. The results of the study Analysis of the Welfare Level of Fishermen in Alue Ambang Village Teunom District Aceh Jaya Regency based on BPS indicators showed that 63.3% of respondents were categorized as medium welfare levels.